Peran PKS Menjadikan Masyarakat Lebih Beretika dan Bermoral Dalam Berpolitik - Husna Siregar; Abdi Abdi; M. Irfan Djailani; Firman Alamsyah; Udzri Hamdi (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Democracy is a word that always fills the conversation of all levels of society, from the lower class to the elite class, namely community leaders, politicians, students, scholars, etc. In addition, democracy is believed to be an alternative value system that develops at the intersection of human life and society, even the state. Democracy is a school of philosophy, namely a school that studies the origins of political power in a country based on the general will of the people. In this case, the nation can be described as a rule of law that evokes the general will and animates the contents of democracy. Following the democratic system, power in the country is in the hands of the people themselves, basically democracy comes from the people, is governed by the people and benefits all the people. From an organizational point of view, democracy means the organization of the State which is carried out by the people themselves or with the consent of the people because sovereignty is in the hands of the people. Another opinion states that democracy is a political system which shows that public policies are determined on the basis of a majority by representatives who are effectively supervised by the people in periodic elections based on the principle of political equality and are held in an atmosphere of guaranteed political freedom. Keywords: Social Justice Party, Society, Ethics, Morals, Politics